AKAR PERMASALAHAN TIDAK TERPENUHINYA PERMINTAAN BABY BUNCIS PERUSAHAAN MITRA OLEH GAPOKTAN WARGI PANGGUPAY - Lathifah Nur; Lucyana Trimo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
According to BPS data (2018), horticultural export volume for the January-December 2018 period had increased about 10% compared to that of 2017. This increase in volume is largely influenced by fresh vegetable exports from West Bandung which reaches 1,500 tons on that year. Supported by local and center government, wide and fertile land in Lembang area, Gapoktan Wargi Panggupay, cultivates baby beans as a superior commodity to meet the demand for baby beans from abroad. The problem often faces by baby bean farmers is in continuity of quantity supplied with export-quality. The purpose of this study is to describe the possible cause of the unfulfilled demand for baby beans by Gapoktan Wargi Panggupay. The aim of this research is the find the root cause why Gapoktan Wargi Panggupay is not always able to meet the demand. The research conducted in Kampung Gandok RT 01 RW 15 Suntenjaya Village, Lembang District, West Bandung Regency, West Java Province. The research design used is a qualitative design with a case study research technique. The data used are primary data and secondary data obtained from in-depth interviews, observation, documentation, and literature. Researchers used qualitative analysis methods with descriptive approaches and fishbone diagrams to find the root of the problem. The results of this study reveal that the root cause of the problem are: (1) farmers perceive the implementation of SOP for baby bean cultivation to be complicated, (2) use of traditional agricultural tools, (3) dry and rainy seasons.